BAGAIMANA KEUNGGULAN BERSAING PELAKU USAHA KULINER YANG DIMEDIASI OLEH DIGITAL MARKETING - Fadiah, Nur; Mustari, Mustari; Rahmatullah, Rahmatullah; Nurdiana, Nurdiana; Inanna, Inanna (Universitas Khairun, 2024)
This research aims to provide insight and knowledge regarding the influence of product quality and innovation on the competitive advantage of culinary business actors in the PTB Maros Regency area by using digital marketing as a moderating factor. This strategy uses descriptive methods combined with quantitative research. The research sample consisted of 100 business actors in the PTB area of Maros Regency. PLS-SEM, or partial least squares structural equation modeling, was used to examine the data. Based on tests conducted on culinary practitioners in the PTB area of Maros Regency, researchers concluded that product quality and innovation have an influence on the use of digital marketing. Innovation and product quality affect a company's ability to compete. Competitive advantage is greatly influenced by the use of digital marketing. You can use digital marketing to make product quality work for you. Gaining a competitive advantage and expressing your product innovation is possible through digital marketing